Implikasi Penerimaan Peserta Didik Baru Berdasarkan Peraturan Menteri Pendidikan dan Kebudayaan Nomor 51 Tahun 2018 - Abidin, Raistin Nur (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
The purpose of this study was to describe the acceptance of new students and analyze the implications of the admission of new students to the zoning system based on the Regulation of the Minister of Education and Culture Number 51 of 2018. This study used a qualitative approach with a descriptive type because the data in the study was stated verbally with descriptive qualifications. The results showed that the acceptance of new students based on the provisions of the Regulation of the Minister of Education and Culture Number 51 of 2018 was carried out through three channels, namely zoning, achievement, and parental assignment. The acceptance of new students in the zoning system in terms of the Regulation of the Minister of Education and Culture Number 51 of 2018 had implications for three things, namely a decrease in learning motivation, an increase in juvenile delinquency, and a lack of parental responsibility towards students.